Molecular wire effects in phenyleneethynylene oligomers: surprising insights - Hergert, Marcel; Bender, Markus; Seehafer, Kai; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
The synthesis and quenching behavior of a series of water-soluble, carboxylate-carrying phenyleneethynylene oligomers—monomer to tetramer—and their polymers are reported; their quenching behavior with different test analytes (paraquat, lead salts, mercury salts, picric acid, methylpyridinium iodide) in water were investigated, and the results were compared to that of the conjugated polymer. Significant but analyte-dependent enhancement effects were found. For monovalent quenchers, only the molecular wire effect applies, but for divalent quenchers multivalency effects are also important.